PERSEPSI NASABAH KARTU KREDIT BCA TENTANG PELAYANAN OLEH PT.DANAMAS INSAN KREASI ANDALAN (DIKA) CABANG BANJARMASIN - Masrifani -; Penta Lestarini Budiati; Alfrida Luter (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, This research aims to determine customer perception of the BCA credit card services, through five service quality dimensions, namely responsiveness, reliability, assurance, empathy and tangibles. The population in this research are all credit card customers BCA totaling 286 people, further samples are taken with a probability sampling method as many as 43 people. Further analysis of data using analysis techniques IPA (Importance-Performance Analysis). The results showed that the general perception of the BCA credit card holders filed attributes of the five dimensions of service quality is positive, meaning that the overall expectations BCA credit card customers for the performance of services provided by PT. Andalan Danamas Insan Creative Banjarmasin Branch has been fulfilled.